Rumah Tinggal Tjong A Fie: Akulturasi dalam Arsitektur Bangunan pada Akhir Abad ke-19 di Kota Medan - Eny Christyawaty (Berkala Arkeologi Sangkhakala, 2011)
AbstractTjong A Fie’s residence is one of the monument of the Colonial buildings are situated on Jl. Ahmad Yani, no. 105, Kesawan, Medan, North Sumatera. The building was built in 1885 to 1900. This paper aims to examine architectural styles that affect Tjong A Fie’s house. Scope of the study include: the pattern layout, layout, construction, decorative ornaments used in. The approach used is qualitative descriptive research. Data collection using direct observation in the field, but it also carried an interview. To deepen the analysis is conducted literature study which related to the topic under study. Sources of data used in this study is artifact and textual. Architectural style Tjong A Fie's house is the result of acculturation of Chinese architecture, Colonial and Malay.